The safety profile of favipiravir should not be the first argument to suspend its evaluation in viral hemorrhagic fevers - Malvy, Denis; Taburet, Anne-Marie; de Lamballerie, Xavier; Mentre, France; Extramiana, Fabrice (PLOS Neglected Tropical Diseases, 2020)
null